Pengaruh Terapi Murottal Al-Qur’an Terhadap Tingkat Stres Kerja Perawat IGD Rumah Sakit Al-Islam Bandung - Rahmat, Rahmat; Mustikaningsih, Dewi; Haryanto, Muklis (Jurnal Keperawatan Profesional, 2019)
Job stress on nurses is one of the problems in human resource management in hospitals. This is because the nurse profession is a health worker who has the highest intensity of interaction with patients and is often faced with situations that can cause work stress. IGD nurses are required to be able to work quickly and precisely in handling emergency patients with different levels of emergency, so it is very susceptible to work stress. One way to overcome the stress of the emergency nurse's work is to listen to murottal Al-Qur'an which is one type of religious therapy. The purpose of this study was to determine the effect of Murottal Al-Qur'an therapy on the stress level of nurse work. This study used quasi pre experimental one group pretest and posttest design. The population of this study were emergency nurses who experienced work stress in the emergency room at Al Islam Hospital Bandung. Samples Total sampling was 28 nurses who were in accordance with the inclusion criteria. The measuring instrument used is the OSI-R (Stupid Inventory-Revised Edition) work stressor (Osipow & Spokane, 1998). The results showed that p Value = 0.025 or p <0.05 so that it could be concluded that murottal Al-Qur'an therapy had an effect on the level of stress of the emergency work nurses at the Al Islam Hospital Bandung. To better know the effect of the greater influence of murottal Al-Qur'an therapy on decreasing the stress level of nurses' work, IGD is expected that further research can use larger samples and longer treatment using a control group. Keywords: Nurse, Job Stress, Murottal Al-Qur'an, IGD